Effects of Chitosan Concentrations in the Chitosan-Alginate Composite on the Quality of Mulberry Caviar during Storage - Uprarawanna, Utsaphong; Jaimun, Ratchadaporn; Kanha, Nattapong (Journal of Food Health and Bioenvironmental Science, 2023)
This research aimed to study the effect of chitosan concentration in the chitosan-alginate composite on the texture profile analysis and sensory properties, the correlation between instrumental and sensory properties, and the qualitative change of mulberry juice caviar (MJC) during storage. MJC with chitosan-alginate composite containing chitosan concentrations of 0, 0.5, 1.0 and 1.5% by-weight (ALG 1.5, CHI 0.5, CHI 1.0 and CHI 1.5, respectively) were prepared by spherification process. The results showed that the MJC formed with CHI 1.5 had the best sensory acceptance scores, while which of CHI 0.5 was easier consumed with lower texture profile analysis (TPA) parameters. Meanwhile, the high positive correlation (> 0.7) between the instrumental textures and sensory scores implied that most consumers favoured MJCs with high springiness, gumminess, and chewiness. In addition, chitosan-alginate composite prolonged the shelf-life of MJCs better than alginate alone, especially refrigeration temperature. CHI 1.5 was the most effective against changes in MJC size and total phenolic content, while CHI 1.0 was the best for preserving total anthocyanin content, 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging and microbiological quality. This product gives a special texture during chewing when adding it into jelly or similar products and it can also use to decorate foods.